(untitled) (Літератури світу: поетика, ментальність і духовність, 2016)
The article deals with child’s gustatory flavours in the terms of poetics. The key attention is paid to the gustatory tastes of a child who being hungry has delirious hallucinations for food. The author of this paper focuses on the story «Oysters» by A. Chekhov. This short story reveals the complex set of psychological and physiological sensations caused by the little child’s hunger. Gustatory fantasies of the hungry child forced him to eat the dish, which he could hardly dream about. The child’s flavoring shock caused by eating oysters eventually leads to stomach disease.